Intubation practice and outcomes among pediatric emergency departments: A report from National Emergency Airway Registry for Children (NEAR4KIDS). (12th January 2022) - Capone, Christine A.; Emerson, Beth; Sweberg, Todd; Polikoff, Lee; Turner, David A.; Adu‐Darko, Michelle; Li, Simon; Glater‐Welt, Lily B.; Howell, Joy; Brown, Calvin A.; Donoghue, Aaron; Krawiec, Conrad; et al.
Abstract: Background: Tracheal intubation (TI) practice across pediatric emergency departments (EDs) has not been comprehensively reported. We aim to describe TI practice and outcomes in pediatric EDs in contrast to those in intensive care units (ICUs) and use the data to identify quality improvement targets. [Correction added on 30 April 2022, after first online publication: The sentence has been modified.] Methods: Consecutive TI encounters from pediatric EDs and ICUs in the National Emergency Airway Registry for Children (NEAR4KIDS) database from 2015 to 2018 were analyzed for patient, provider, and practice characteristics and outcomes: adverse TI‐associated events (TIAEs), oxygen desaturation (SpO2 < 80%), and procedural success. A multivariable model identified factors associated with TIAEs in the ED. Results: A total of 756 TIs in 13 pediatric EDs and 12, 512 TIs in 51 pediatric/cardiac ICUs were reported. Median (interquartile range [IQR]) patient age for ED TIs was higher (32 [7–108] months) than that for ICU TIs (15 [3–91] months; p < 0.001). Proportion of TIs for respiratory decompensation (52% of ED vs. 64% ICU), shock (26% vs. 14%), and neurologic deterioration (30% vs. 11%) also differed by location. Limited neck mobility was reported more often in the ED (16% vs. 6%). TIs in the ED were performed more often via video laryngoscopy (64% vs. 29%). Adverse TIAE rates (15.6% ED, 14% ICU; absolute difference = 1.6%, 95% confidence interval [CI] = –1.1 to 4.2; p = 0.23) and severe TIAE rates (5.4% ED, 5.8% ICU; absolute difference = –0.3%, 95% CI = –2.0 to 1.3; p = 0.68) were not different. Oxygen desaturation was less commonly reported in ED TIs (13.6%) than ICU TIs (17%, absolute difference = –3.4%, 95% CI = –5.9 to –0.8; p = 0.016). Among ED TIs, shock as an indication (adjusted odds ratio [aOR] = 2.15, 95% CI = 1.26 to 3.65) and limited mouth opening (aOR = 1.74, 95% CI = 1.04 to 2.93) were independently associated with TIAEs. Conclusions: While TI characteristics vary between pediatric EDs and ICUs, outcomes are similar. Shock and limited mouth opening were independently associated with adverse TI events in the ED.